2021
DOI: 10.1093/plphys/kiab528
|View full text |Cite
|
Sign up to set email alerts
|

CO2-dependent migration and relocation of LCIB, a pyrenoid-peripheral protein in Chlamydomonas reinhardtii

Abstract: Most microalgae overcome the difficulty of acquiring inorganic carbon (Ci) in aquatic environments by inducing a CO2-concentrating mechanism (CCM). In the green alga Chlamydomonas reinhardtii, two distinct photosynthetic acclimation states have been described under CO2-limiting conditions (low-CO2 [LC] and very low-CO2 [VLC]). LC-inducible protein B (LCIB), structurally characterized as carbonic anhydrase, localizes in the chloroplast stroma under CO2-supplied and LC conditions. In VLC conditions, it migrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Its genome has been sequenced multiple times by several laboratories [ 42 , 43 ]. It has also been used for several transcriptome analyses [ 12 , 23 ] and is an often-preferred background strain for photosynthesis- or stress-related experiments [ 25 , 44 , 45 , 46 ]. CC-5325 is relatively new, available to the Chlamydomonas community since 2014 [ 47 ], but has been frequently used because it is the background strain of the Chlamydomonas CLiP mutant Library [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its genome has been sequenced multiple times by several laboratories [ 42 , 43 ]. It has also been used for several transcriptome analyses [ 12 , 23 ] and is an often-preferred background strain for photosynthesis- or stress-related experiments [ 25 , 44 , 45 , 46 ]. CC-5325 is relatively new, available to the Chlamydomonas community since 2014 [ 47 ], but has been frequently used because it is the background strain of the Chlamydomonas CLiP mutant Library [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LCIB helps to maintain an inward CO 2 diffusion gradient while increasing the overall stromal Ci concentration. In ambient CO 2 , LCIB is dispersed throughout the chloroplast stroma in a multimeric complex with low CO 2 -inducible C (LCIC) ( Yamano et al, 2010 , 2021 ). In support of its critical role, LCIB knockout mutants are unable to grow or assimilate CO 2 in ambient CO 2 , whereas knockout mutations in LCIC appear to have no identifiable impact on growth or photosynthesis (Spalding, unpublished).…”
Section: Chlamydomonas Has Two Distinct Ccm Settingsmentioning
confidence: 99%
“…Post-translational modification and Ca 2+ signaling are both implicated in regulating the transition between Ci uptake pathways at ambient or sub-ambient CO 2 , although current knowledge is somewhat fragmented. The migration of LCIB to the pyrenoid periphery is dependent on light and LCIC, and may be regulated by phosphorylation of itself, and/or LCIC within the LCIB/C complex ( Jin et al, 2016 ; Yamano et al, 2021 ). Recent work has also highlighted the importance of the starch sheath in facilitating the migration of LCIB and CCM function ( Toyokawa et al, 2020 ).…”
Section: Ccm Regulation In Chlamydomonasmentioning
confidence: 99%
“…It has been suggested that the chloroplast protein limiting CO 2 inducible protein B (LCIB), which structurally resembles a β-type carbonic anhydrase ( Jin et al., 2016 ), is indispensable for the stimulation of CO 2 uptake under LC conditions ( Yamano et al., 2010 ; Wang and Spalding, 2014 ). It may be that LCIB captures CO 2 leaked from the pyrenoid by unidirectionally hydrating CO 2 to HCO 3 - under LC conditions ( Yamano et al., 2022 ), though recombinant LCIB did not show carbonic anhydrase activity ( Jin et al., 2016 ). LCIB proteins are dispersed uniformly in the chloroplast under LC conditions, whereas they migrate to the pyrenoid periphery under VLC conditions ( Yamano et al., 2022 ).…”
Section: Carbon Fixation Capacity Assisted By Co 2 ...mentioning
confidence: 99%
“…It may be that LCIB captures CO 2 leaked from the pyrenoid by unidirectionally hydrating CO 2 to HCO 3 - under LC conditions ( Yamano et al., 2022 ), though recombinant LCIB did not show carbonic anhydrase activity ( Jin et al., 2016 ). LCIB proteins are dispersed uniformly in the chloroplast under LC conditions, whereas they migrate to the pyrenoid periphery under VLC conditions ( Yamano et al., 2022 ). The starch sheath surrounding the pyrenoid is important in the localization of LCIB ( Toyokawa et al., 2020 ).…”
Section: Carbon Fixation Capacity Assisted By Co 2 ...mentioning
confidence: 99%